REAKSI PASAR SEBELUM DAN SESUDAH STOCK SPLIT - mayangsari, ni luh astrid; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen; Vol 11 No 4 (2022)DO - 10.24843/EJMUNUD.2022.v11.i04.p09, 2022)
Stock split is an activity that can be carried out by companies that have gone public as an effort to increase the quantity of outstanding shares. When the stock price is overvalued, a stock split is carried out. This makes traded in the market less active. This study aims to analyze the differences liquidity and abnormal returns both before and after the stock split. Which in this study has a population of 57 companies on the Indonesia Stock Exchange that conducted a stock split for the 2014-2018 period, taking stock using the census. This research is a quantitative using the t-test test data analysis method. Based on the analysis that the researcher has done, it is found that there is a difference liquidity, where the stock liquidity value before the stock split is greater than the stock liquidity after the stock split; there is a difference in the abnormal return value, where the average value of the abnormal return of the stock before the stock split is greater than the abnormal return of the stock after the stock split. Keywords :  Liquidity; Abnormal Return; Stock Split; Market Reaction; Indonesia Stock Exchange